PENGARUH BIMBINGAN PRIBADI-SOSIAL TERHADAP KEMATANGAN EMOSI - Djarot Sumarwoto, Vitalis (Jurnal Pendidikan, 2012)
Emotional maturity of an individual sticks and grows in line with his/her physical growth, including that of Secondary School students. Their emotional development can be viewed through general activities they conduct. There are some factors which assumptively promote their emotional maturity, but they can be mainly grouped into two categories, i.e. internal and external ones. The internal factors can be sub-grouped into physical and psychological ones. Physical factor develops in line with the age, where the older they are, the better their body builds are. The psychological development will none theless follows this physical growth, so as to become more emotionally mature. One of the external factor which can influence the development of thei emotional maturity is the school counceling practice. The main school counceling practice serves problem solving in the area of students individual conduct in relation to others. The school counceling office is in charge of assisting the students emotional development to reach their emotional maturity.Key words:Â Social-individual Counceling, Emotional Maturity